Penerapan Pasal 32 Ayat (2) PP 24 Tahun 1997 Tentang Pendaftaran Tanah Mengenai Asas Rechtsverwerking - Islam, Andi Abdi; Nawi, Syahruddin; Risma, Andi (Journal of Lex Philosophy (JLP), 2024)
Tujuan penelitian menganalisis Penerapan Pasal 32 Ayat (2) PP 24 Tahun 1997 Tentang Pendaftaran Tanah Mengenai Asas Rechtsverwerking dan untuk mengetahui, menganalisis, dan menjelaskan Faktor-Faktor apa yang mempengaruhi Penerapan Pasal 32 Ayat (2) PP 24 Tahun 1997 Tentang Pendaftaran Tanah Mengenai Asas Rechtsverwerking. Penelitian ini menggunakan tipe penelitian hukum empiris. Hasil Penelitian ini menunjukkan bahwa: (1) Penerapan Pasal 32 Ayat (2) PP 24 Tahun 1997 Tentang Pendaftaran Tanah Mengenai Asas Rechtsverwerking dapat dilihat dari Eksistensi dan Pengaturan Asas Rechtsverwerking dalam Pendaftaran Tanah di Indonesia, juga bagaimana persyaratan Penerapan Asas Rechtsverwerking dalam peraturan Perundang-undangan, selain itu Asas Rechtsverwerking juga telah diterapkan dalam Yurisprudensi serta dalam kasus pertanahan di Kabupaten Wajo. dan (2) Bahwa terdapat beberapa Faktor yang mempengaruhi Penerapan Pasal 32 Ayat (2) PP 24 Tahun 1997 Tentang Pendaftaran Tanah Mengenai Asas Rechtsverwerking di Kabupaten Wajo, yang pertama adalah Faktor Substansi Hukumnya dan yang kedua adalah Faktor Struktur Hukumnya. The research objective is to analyze the Application of Article 32 Paragraph (2) of PP 24 of 1997 concerning Land Registration Regarding Rechtsverwerking Principles and to find out, analyze and explain what factors influence the Application of Article 32 Paragraph (2) of PP 24 of 1997 concerning Land Registration Regarding Principles Rechtsverwerking. This research uses an empirical type of legal research. The results of this research show that: (1) The application of Article 32 Paragraph (2) PP 24 of 1997 concerning Land Registration regarding the Rechtsverwerking Principle can be seen from the existence and regulation of the Rechtsverwerking Principle in Land Registration in Indonesia, as well as the requirements for the Implementation of the Rechtsverwerking Principle in statutory regulations. invitation, apart from that the Rechtsverwerking Principle has also been applied in Jurisprudence and land cases in Wajo Regency. and (2) That several factors influence the implementation of Article 32 Paragraph (2) PP 24 of 1997 concerning Land Registration Regarding the Rechtsverwerking Principle in Wajo Regency, the first is the Legal Substance Factor and the second is the Legal Structure Factor